The Impact of Rupiah Exchange Rate and Crude Palm Oil (CPO) Export Value on the Gross Regional Domestic Product (GRDP) of Lampung Province: An Islamic Economic Perspective, 2013-2022 - Anggraini, Dini; Ghofur, Ruslan Abdul; Nurmalia, Gustika (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
GRDP in Lampung province is still experiencing fluctuations, which has increased from 2013-2019. Then, in 2020 GRDP will decrease and will increase again in 2021-2022. The research method used is quantitative. The data source used in compiling this research is secondary data in the form of a time series, which was processed using EViews 10. Data obtained from BPS Lampung province includes data on the rupiah exchange rate, the value of CPO exports and the GRDP of Lampung province in 2013-2022. The results showed that partially, the rupiah exchange rate variable had a positive and significant effect on the GRDP in Lampung province in 2013-2022, and the CPO export value variable had no significant effect on the GRDP in Lampung province in 2013-2022. Meanwhile, the f (simultaneous) test shows that the rupiah exchange rate and the value of CPO exports jointly affected GRDP in Lampung province in 2013-2022. GRDP, in the perspective of Islamic economics, will affect tax revenues by increasing waqf, zakat, alms and other income taxes which will have a good impact because increasing regional revenue is expected to increase welfare and economic growth.